Undetectable Troponin I at Presentation Using a Contemporary Assay does not Rule Out Myocardial Infarction. Issue 1 (January 2014) - Kelly, AM
Objective: Chest pain is a common reason for presentation to emergency departments (ED). Recent evidence suggests that an undetectable troponin level at ED presentation can rule out the presence of myocardial infarction (MI). The aim of this study was to externally validate that finding using a troponin I (TnI) assay. Methods: Unplanned sub-study of a prospective observational cohort study of patients presenting to ED with chest pain without electrocardiogram evidence of ischaemia who underwent a 'rule out' acute coronary syndrome process. Clinical, investigational and outcome data were collected. Primary outcome of interest was diagnostic accuracy for type I MI at index visit. Results: 685 patients were studied; median age 62, 60% male. Two hundred and seventeen had an undetectable TnI at ED presentation. There were two non-ST elevation myocardial infarctions in the group (2/217, 0.9%, 95% CI 0.16-3.6%). Sensitivity of undetectable TnI for ruling out type I MI was 98. 2% (99% CI 92.9-99.7%) with negative predictive value of 99.1% (96.4-99.8%). Conclusion: Approximately 1% of patients with an undetectable TnI at ED presentation were diagnosed with a type I MI. An undetectable initial TnI using a contemporary sensitive TnI assay does not safely exclude MI in an ED chest pain cohort. (Hong Kong j.emerg.med. 2014;21:31-36)